Supersapientia: Berthold of Moosburg and the Divine Science of the Platonists - King, Evan (History of Metaphysics: Ancient, Medieval, Modern, 2021)
This study examines the motivations and doctrinal coherence of the Commentary on the Elements of Theology of Proclus written by Berthold of Moosburg, O.P. († c. 1361/1363). It provides an overview of Berthold's biography and intellectual contexts, his manuscript remains, and a partial edition of his annotations on Macrobius and Proclus. Through a close analysis of the three prefaces to the Commentary, giving special attention to Berthold's sources, it traces the Dominican's elaboration of Platonism as a soteriological science. The content of this science is then presented in a systematic reconstruction of Berthold's cosmology and anthropology. The volume includes an English translation of the three fundamental prefaces of the Commentary.. Readership: Students and specialists of medieval philosophy and the history of Platonism, especially those interested in the influence of late-antique Neoplatonism on medieval natural philosophy and theories of contemplation.